ANALISIS TINGKAT PENGANGGURAN TERBUKA DI PROVINSI SULAWESI UTARA TAHUN 2015-2025 - Hanafi Ardiansyah; Muhammad Nur Iman; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the trend of the Open Unemployment Rate (TPT) in North Sulawesi Province for the 2015–2025 period and identify the facto”s influencing its changes. The method used is a quantitative descriptive approach with time series analysis techniques to observe the pattern of TPT development over time. The data source used is secondary data obtained from the official publication of the Central Statistics Agency (BPS) through the National Labor Force Survey (Sakernas), which is consistently used to describe employment conditions in Indonesia. The results show that the TPT trend in North S”lawe’i is fluctuating but tends to decline in the long term, with a significant increase during the COVID-19 pandemic period which resulted in a decrease in labor absorption. After that period, the TPT again experienced a decline along with economic recovery and increased activity in the informal and formal sectors. These findings confirm that unemployment dynamics are strongly influenced by macroeconomic conditions, labor market structure, and the absorption capacity of the business sector. The main implication of this study is the need for more adaptive and data-driven employment policies, especially in improving the quality of the workforce and expanding employment opportunities based on regional potential. The novelty of this research lies in the analysis of long-term trends that integrate the impact of the global crisis on unemployment dynamics at the provincial level in a m’re contextual and empirical manner.